Identifying SOX2-OT transcript that is responsible for regulating SOX2 in cancer cells and embryonic stem cells - Dao-Yin Dong; Pu-Yu Li (Research Ideas and Outcomes, 2021)
SOX2 overlapping transcript (SOX2-OT) is an evolutionarily conserved long non-coding RNA (lncRNA) whose intronic region contains the transcript of pluripotency gene SRY-box transcription factor 2 (SOX2). It has been suggested that SOX2-OT can regulate its overlapping gene, SOX2. Studies demonstrated that elevated SOX2-OT promotes SOX2 expression in cancer cells, whereas levels of SOX2-OT are inversely correlated with levels of SOX2 in embryonic stem cells. It is not clear why there is a tremendous discrepancy in the regulation of SOX2 by SOX2-OT in cancer cells and embryonic stem cells. Due to the diversified transcription of the SOX2-OT gene, we hypothesize that differential expression of transcripts of the SOX2-OT gene in cancer cells and embryonic stem cells may contribute to the divergence in the regulatory relationship of SOX2-OT and SOX2. A CRISPR screening platform can be leveraged to systemic evaluate which transcript of the SOX2-OT gene may be responsible for upregulation or downregulation of SOX2 in cancer cells and embryonic stem cells, respectively.